2017
DOI: 10.1080/2162402x.2017.1380764
|View full text |Cite
|
Sign up to set email alerts
|

Co-stimulatory signaling determines tumor antigen sensitivity and persistence of CAR T cells targeting PSCA+ metastatic prostate cancer

Abstract: Advancing chimeric antigen receptor (CAR)-engineered adoptive T cells for the treatment of solid cancers is a major focus in the field of immunotherapy, given impressive recent clinical responses in hematological malignancies. Prostate cancer may be amenable to T cell-based immunotherapy since several tumor antigens, including prostate stem-cell antigen (PSCA), are widely over-expressed in metastatic disease. While antigen selectivity of CARs for solid cancers is crucial, it is problematic due to the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(165 citation statements)
references
References 45 publications
7
155
3
Order By: Relevance
“…87 Similarly, PSCA-directed CARs utilizing a 4-1BB costimulatory domain demonstrated activity only in response to cells expressing high levels of the antigen, whereas CARs utilizing a CD28 costimulatory domain were able to target cells expressing either high or low levels of the PSCA antigen. 37 Interestingly, these findings correlate with the kinetics of CAR T cell responses in vivo which may reflect the relative sensitivity of each CAR. 88 As these findings are currently limited to a few models, further studies are needed to determine if these findings are generalizable to all CAR constructs and how this can be incorporated into CAR T cell therapy to reduce the occurrence of antigen low relapse.…”
Section: Role Of Car Structure In Antigen Sensitivitymentioning
confidence: 83%
See 1 more Smart Citation
“…87 Similarly, PSCA-directed CARs utilizing a 4-1BB costimulatory domain demonstrated activity only in response to cells expressing high levels of the antigen, whereas CARs utilizing a CD28 costimulatory domain were able to target cells expressing either high or low levels of the PSCA antigen. 37 Interestingly, these findings correlate with the kinetics of CAR T cell responses in vivo which may reflect the relative sensitivity of each CAR. 88 As these findings are currently limited to a few models, further studies are needed to determine if these findings are generalizable to all CAR constructs and how this can be incorporated into CAR T cell therapy to reduce the occurrence of antigen low relapse.…”
Section: Role Of Car Structure In Antigen Sensitivitymentioning
confidence: 83%
“…Each of these costimulatory domains have proven sufficient in promoting effective CAR T cell responses in vivo in various preclinical models and clinical trials, however, the incorporation of the 4-1BB domain has demonstrated a significant impact on the in vivo persistence of CAR T cells. 34,36,37 This has been most notable when comparing CAR T cells targeting CD19-positive leukemia with either the CD28 or the 4-1BB costimulatory domain. In pediatric patients with relapsed/ refractory ALL, treatment with a CD28-CAR resulted in persistence which was limited to approximately 2 months in patients achieving remission.…”
Section: Anti G En P Os Itive E Sc Ape and C Ar T Cell Per S Is Ten Cementioning
confidence: 99%
“…T-cell isolation, lentivirus production and transduction, and ex vivo expansion of CAR T cells was performed as previously described 23 .…”
Section: Human T Cell Enrichment Lentivirus Production and Transductmentioning
confidence: 99%
“…Flow cytometric analysis was performed as previously described 23 . Tumor cells were identified using Ep-CAM (CD326) (BioLegend, Clone: 9C4).…”
Section: Intracellular/extracellular Staining and Flow Cytometrymentioning
confidence: 99%
“…PBT030 endogenously expresses high level of IL13Ra2. HT1080 and PBT138 do not express IL13Ra2 and were lentivirally engineered to express varied levels based on different promoter strengths to investigate the relationship between killing kinetics and antigen expression level: High (>70% + ) driven by the EF1a promoter, Medium (between 40% + -70% + ) driven by the PGK promoter, Low (<20% + ) driven by the attenuated PGK100 promoter [35,36]. These cell lines are denoted with H, M, L respectively e.x.…”
Section: Cell Linesmentioning
confidence: 99%